(untitled) (Hematology Meeting Reports, 2009)
Todate, therapy-related myelodysplastic syndromes/acute Myeloid Leukemias (t-MDS/ AML) represent the main long-term adverse effect of cancer treatment. The identification of new prognostic factors has raised the question whether reducing treatment intensity in good prognosis patients may save them from long term-toxicity, without impairing response rates.